Dobrostan dzieci wychowywanych przez kohabitujących rodziców. Co wynika z badań dotyczących znaczenia struktury rodziny dla rozwoju dzieci? - Jankowiak, Barbara (Studia Edukacyjne, 2019)
Due to the changes in the modern family, many children are brought up in non-traditional families. Cohabitation is one of the alternative forms of the family. The results of the studies on the welfare of children raised in cohabitation relationships are not conclusive, yet the data indicate poorer developmental achievements of these children in comparison with children brought up by married couples are predominant. The article presents the results of research which compares the welfare of children in different forms of relationships and points to three possible reasons for lower developmental achievements of children raised by cohabiting partners. These include: characteristics of the partners, characteristics of the cohabitation relationships and the way of selecting a group for a study which compares the welfare of children in different forms of families, connecting cohabiting partners who are the child’s biological parents with those persons forming cohabitation relationships in which only one of the partners is the child’s natural parent.